The variable income marjet and sanitation branch companiel: the impact os investments associated with the New Sanitation Marl (Research, Society and Development, 2020)
This article aims to carry out an analysis of companies in the sanitation sector in Brazil, the progress of the implementation of the country's sanitation project, with the visible impact of investments applied to the New Sanitation Framework (Federal Law no. 14.026/2020). A bibliographic research was carried out through works on the topic that have impacts in addition to social and economic, mainly from the sanitation sector in the stock market, which is a rule for the sanitation sector in general. The economic impact generated by this project and the real importance of the investments of these amounts invested were analyzed taking into account a future projection with the proposed formulas, the intrinsic value of an asset, as well as its projected market value. The growth in the sanitation sector in the next ten years can be predicted through its actions, with an average development in its market value of 154.78%, as well as growth in the main fundamentalist indicators of related assets, thus generating many benefits and bonuses.